Determination of Some Heavy Metal Levels in Muscle Tissues of Lake Van Fish (Chalcalburnus tarichi) - Kilicel, Fevzi; Gokalp, Faik (Asian Journal of Chemistry, 2016)
Some heavy metal (Zn, Pb, Cd, Cr, Ni, Co, Bi, Mn, Cu) concentrations in the muscle tissues of Lake Van fish (Chalcalburnus tarichi) were measured and compared with sea fish. Metal concentration in muscles was investigated by linear regression analysis. Concentration (as μ/g dry weight) was highest for Zn (1.806 ± 0.553) and lowest for Cd (0.032 ± 0.014). Cu was not measured. The highest concentration of Zn (3.02), Pb (0.09), Cd (0.06), Cr (0.09), Ni (0.44), Co (0.26), Bi (0.64) and Mn (0.42) were measured in muscle tissues of Lake Van fish (Chalcalburnus tarichi).